Quality of life and associated factors among patients with cancer receiving chemotherapy at Dessie Comprehensive Specialized Hospital, North-East Ethiopia: a cross-sectional study - Bayked, Ewunetie Mekashaw; Yimam, Mekdes Getachew; Yalew, Zemen Mengesha; Toleha, Husien Nurahmed; Zewdie, Segenet (Frontiers in Oncology, 2024)
Background: Cancer is a major public health problem around the world. Cancer by itself and its treatment modalities affect the quality of life (QoL) of patients with it. However, there were a paucity of studies about the QoL of patients receiving chemotherapeutic treatment in Ethiopia. This study was aimed at addressing such a gap. Accordingly, we investigated QoL and associated factors among cancer patients receiving chemotherapy at Dessie Comprehensive Specialized Hospital (DCSH), North East Ethiopia, in 2023. Methods: We employed a cross-sectional study from April 1 to May 30, 2023. The data was collected using the European Organization for Research and Treatment of Cancer Core QoL Questionnaire, version 3.0 (EORTC QLQ-C30). The data was entered and cleaned using EpiData version 4.6 and exported to Statistical Package for Social Sciences (SPSS) version 27 for analysis. The association between the dependent and independent variables was determined using Odds Ratios (ORs) at a p value < 0.05 with a 95% CI. Results: Data was collected from 394 patients. Their mean summary QoL score was 36.3 ± 9.0. About 39.3% demonstrated a good QoL summary score, whereas 60.7% were impacted by symptoms. A good functional QoL score was observed in 42.6% of the participants. About 54.8% and 31.7% reported good overall health status and good overall QoL, respectively. The most impacted functional domain was social functioning, affecting 64.5% of participants. The most common symptom was diarrhea, affecting 65.5% of the participants. Secondary school education level (Adjusted Odds Ratio-AOR = 3.16, 95% CI: 1.14-8.81), diploma and above education level (AOR = 4.90, 95% CI: 1.29-18.62), and urban residency (AOR = 1.74, 95% CI: 1.07-2.82) had a significant positive association with QoL, while being a civil servant (AOR = 0.13, 95% CI: 0.04-0.49), having stage III cancer (AOR = 0.14, 95% CI: 0.05-0.39), and stage IV cancer (AOR = 0.16, 95% 0.06-0.44) had a significant negative association with it. Conclusion: The QoL for cancer patients undergoing chemotherapy was significantly low and associated with their level of education, occupational status, area of residence, and stage of cancer. Incorporating psychosocial support is thus crucial in their treatment plans.